Ketoleranan Bibit Jeruk Terhadap Garam NaCI. (Tolerance of citrus seedlings to sodium chloride). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1984)
ABSTRAK Citrus plants are cultivated intensively throughout Indonesia. The plants are mostly grown on the fertile soils. In order to be able to extend the cultivation area to low fertility soils and the saline soils selection of tolerance citrus species for the adverse condition is required. This experiment was carried out to study the effect of NaCI solution on seedlings of Citrus reticulata Blanco and Citrus grandis L. The seed of C. reticulate is poly-embrionic and the seed of C. grandis is mono-embrionic. The concentration of NaCI solutions used were 0 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 100 ppm and 2000 ppm. The results showed that the Citrus grandis L. seedlings were more tolerant to high NaCI concentration than those of the Citrus reticulata Blanco. It indicates that mono-embrionic seeds are more tolerant to salinity than poly embrionic seeds.